2008
DOI: 10.1016/j.biocel.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-2 binding to the thrombospondin-1 type III repeats, a novel antiangiogenic domain

Abstract: Thrombospondin-1, an antiangiogenic matricellular protein, binds with high affinity to the angiogenic fibroblast growth factor-2, affecting its bioavailability and activity. The present work aimed at further locating the fibroblast growth factor-2 binding site of thrombospondin-1 and investigating its activity, using recombinant thrombospondin-1 proteins. Only recombinant constructs containing the thrombospondin-1 type III repeats bound fibroblast growth factor-2, whereas other domains, including the known ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 28 publications
(48 reference statements)
0
47
0
1
Order By: Relevance
“…It acts through multiple mechanisms, including direct interaction with endothelial cell receptors and sequestration of angiogenic factors and proteases. [26][27][28][29][30] TSP-1 is a critical determinant of angiogenesis, dormancy and growth in different types of sarcomas. [18][19][20]31 In agreement with this suppressive activity, TSP-1 expression is downregulated in highly vascularized sarcomas, including myxoid liposarcoma, [17][18][19] and its induced expression impairs the in vivo growth of Ewing's sarcoma models.…”
Section: Discussionmentioning
confidence: 99%
“…It acts through multiple mechanisms, including direct interaction with endothelial cell receptors and sequestration of angiogenic factors and proteases. [26][27][28][29][30] TSP-1 is a critical determinant of angiogenesis, dormancy and growth in different types of sarcomas. [18][19][20]31 In agreement with this suppressive activity, TSP-1 expression is downregulated in highly vascularized sarcomas, including myxoid liposarcoma, [17][18][19] and its induced expression impairs the in vivo growth of Ewing's sarcoma models.…”
Section: Discussionmentioning
confidence: 99%
“…46 Another region of TSP-1, designated the type 3 repeats, inhibits angiogenesis by directly binding and sequestering fibroblast growth factor-2. 47 TSP-1, through its C-terminal domain, binds CD47; this leads to various events that alter angiogenesis, which include the disruption of constitutive association between CD47 and VEGFR2 48 as well as the inhibition of VEGF-dependent NO signaling. 49 There are 3 TSRs in TSP-1 and TSP-2.…”
mentioning
confidence: 99%
“…Thrombin-generated, proteolytic fragments of TSP-1 were first used, and showed that the FGF-2-binding ability was retained by the 140 kDa carboxy-terminal domain [29,30]. Using recombinant portions of TSP-1, we identified a previously undescribed antiangiogenic site in the type III repeats of TSP-1, and demonstrated that binding of the angiogenic factor FGF-2 to this site inhibits angiogenesis by sequestration of FGF-2 [31]. Finally, the peptide array technology allowed us to identify three potentially active linear sequences involved in the interaction of FGF-2 with the type III repeats of TSP-1 [68].…”
Section: Exploitation Of the Fgf-2-binding Sequence Of Tsp-1 For The mentioning
confidence: 99%
“…TSP-1 binds FGF-2, with high affinity (in the nanomolar range), similar to the affinity of the growth factor for heparin [29,31]. Consequently to this interaction, TSP-1 prevents FGF-2 binding to HSPG in the extracellular matrix and on the surface of endothelial cells [30], inhibiting FGF-2-mediated pro-angiogenic activation of endothelial cells, and depleting the extracellular matrix of stored FGF-2, an important component in the process of neovascularization [29,30].…”
Section: Exploitation Of the Fgf-2-binding Sequence Of Tsp-1 For The mentioning
confidence: 99%
See 1 more Smart Citation